OK SEBA Keroncong Reinterpretation in Digital Space: Repertoire & Arrangement Strategies - Natanael Dwi Kusbayudana; Abdul Rachman (Universitas Negeri Surabaya, 2026)
The rapid development of digital media has transformed the ways music is produced, distributed, and consumed, requiring traditional music genres, including keroncong, to adapt to contemporary trends and audience behaviors across digital platforms. This phenomenon is exemplified by OK SEBA (Orkes Keroncong SEBA), which actively reinterprets popular songs through repertoire adaptation and arrangement strategies to engage broader audiences. This study aims to analyze OK SEBA's performance practices in the digital space and examine the strategies employed in adapting its repertoire and musical arrangements. A qualitative research design with a case study approach and musicological analysis was employed. Data were collected through participant observation, in-depth interviews, and document analysis. The findings reveal that OK SEBA's reinterpretation of keroncong music in the digital space is realized through the adaptation of repertoire and musical arrangements. Repertoire adaptation involves combining currently trending popular songs with nostalgic classics to appeal to diverse audience segments. Arrangement strategies include the transformation of instrumentation, melodic elaboration, musical intertextuality, and the reconstruction of rhythmic patterns while preserving the original identity of each song within the aesthetic idiom of keroncong. These findings suggest that the sustainability of keroncong music in the digital era depends on musicians' ability to creatively reinterpret musical works without compromising the genre's traditional identity.